1991
DOI: 10.1073/pnas.88.15.6883
|View full text |Cite
|
Sign up to set email alerts
|

Allografts of tumor nuclear transplantation embryos: differentiation competence.

Abstract: The developmental potential of nuclei can be studied by nuclear transplantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

1993
1993
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…More convincingly, injection of the nuclei isolated from the Lucké renal cancer cells of the frog origin into enucleated frog eggs allows the eggs to hatch out tadpoles that are normal without any trace of cancer (Fig. 4) [285,[662][663][664][665][666][667][668]. Similar conversion back to a normal state by an embryonic microenvironment has also been shown for a few other cancer cell types [448, 669-673, 673, 674].…”
Section: Actually Whether Mutation Is Needed or Not For Tumor Formatmentioning
confidence: 81%
“…More convincingly, injection of the nuclei isolated from the Lucké renal cancer cells of the frog origin into enucleated frog eggs allows the eggs to hatch out tadpoles that are normal without any trace of cancer (Fig. 4) [285,[662][663][664][665][666][667][668]. Similar conversion back to a normal state by an embryonic microenvironment has also been shown for a few other cancer cell types [448, 669-673, 673, 674].…”
Section: Actually Whether Mutation Is Needed or Not For Tumor Formatmentioning
confidence: 81%
“…The Lucké cancer nucleus after transplantation into enucleated eggs directed, in the best cases, the formation of swimming tadpoles (King and DiBerardino, 1965; McKinnell et al, 1969). More recently, Lust et al (1991) reported that allografts from tumor nuclear transplants on normal hosts differentiated into a variety of tissues equivalent to that in the 50‐day old hosts that were about two‐thirds of the way toward metamorphosis. These studies demonstrated that the normal genes in a cancer genome responded to the “differentiation inducers” in an embryonic system and their “cancer genes” were repressed.…”
Section: Other Applications and Genetic Modificationsmentioning
confidence: 99%
“…Significant concerns arose in the 1960s as transplanted nuclei containing the genetic information from frog renal cancer cells into enucleated eggs resulted in various normal tissue without cancer [28] and that this was not due to primary "irreversible changes that prevent them from responding to the host environment" [29]. The weakness in the SMT was pointed out some 40 years ago and again more recently [30,31].…”
Section: Somatic Mutation Theory (Smt)mentioning
confidence: 99%